Changes in physiological and some nutritional, nutraceuticals, chemical–physical, microbiological and sensory quality of minimally processed cactus pears cvs 'Bianca', 'Gialla' and 'Rossa' stored under passive modified atmosphere. (12th October 2017) - Palma, Amedeo; Continella, Alberto; La Malfa, Stefano; D'Aquino, Salvatore
Abstract: BACKGROUND: The objective of this study was to compare the overall quality changes of minimally processed cactus pears cvs 'Bianca', Gialla' and 'Rossa' stored at 4 °C for 10 days. Periodically in‐package CO2, O2 and C2 H4 were determined and fruit were assessed for overall quality changes (pH, acidity, sugars, phenolics, betacyanins and betaxanthines, antioxidant capacity, colour, firmness, microbiological population and sensory attributes). In a preliminary study three different polymeric films were tested to select the most suitable to design a package with a short lag time to achieve steady‐state conditions. RESULTS: Results showed marked differences between measured in‐package CO2 and O2 values and those calculated based on respiration of peeled fruit and film permeance to CO2 and O2 provided by manufactures. The sensory evaluation of packed fruit indicated in film BBT‐Bolphane, which created a steady‐state in‐package partial pressure for CO2 of 4.3–4.8 kPa and for O2 of 4.8–5.5 kPa, as the best film. Results of in‐package gas composition with the three cultivars were similar to those achieved in cv. 'Gialla' with the preliminary test. All measured qualitative parameters changed slightly over the storage period for all cultivars and followed the same trend, despite significant differences existing among cultivars. CONCLUSION: This study clearly showed a similar physiological behavior of minimally processed 'Bianca', 'Gialla' and 'Rossa' cactus pears. Storage conditions optimal for one cultivar fit well for the others; thus mixing fruit of different cultivars in a package designed for one specific cultivar does not lead to relevant deviation from expected results. © 2017 Society of Chemical Industry